Application of cellulose plate modified with encapsulated Cinnamomum zelanicum essential oil in active packaging of walnut kernel. (1st July 2022) - Erfani, Aref; Khalil Pirouzifard, Mir; Almasi, Hadi; Gheybi, Nesa; Pirsa, Sajad
Highlights: Encapsulation of Cinnamomum zelanicum essential oil. Modification of cellulose plate. Simultaneous active and vacuum packaging of walnut kernel. Sensorial and oxidative control of walnut kernel. Abstract: In this study, Cinnamomum zelanicum essential oil was encapsulated with β-cyclodextrin and sodium caseinate (EO/BCD/Ca) and nanoemulsion was optained. In order to encapsulation of essential oil, different formulations of nanoemulsions containing essential oil were produced by ultrasound method and the effect of different polymers on the particle size and turbidity of the nanoemulsion was investigated. Scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR) techniques were used to study the structure and morphology of the produced nanoemulsions. Cinnamomum zelanicum essential oil encapsulated with β-cyclodextrin and sodium caseinate was used to modify porous cellulose plates (Cel/EO/BCD/Ca). Cellulose/encapsulated essential oil plates were used to package the walnut kernel to control oxidative changes during storage. The effect of packaging type (under vacuum and ordinal), plate type and storage time on quality control of walnut kernel and oil extracted from walnut kernel was investigated. The results showed that the particle size of essential oil, essential oil/β-cyclodextrin and essential oil/β-cyclodextrin/sodium caseinate were in the range of 84–85, 713–713 and 237–234 (nm), respectively. The encapsulation efficiency of both formulations was above 70%. Zeta potential was negative for essential oil/β-cyclodextrin/sodium caseinate samples and free essential oil samples. The effect of different polymers on the turbidity of emulsions was significant. The results of sensory evaluation of walnut kernel showed that the use of encapsulated essential oil compared to free essential oil caused the protection of color, taste and other quality characteristics during storage. Also, the essential oil encapsulated with β-cyclodextrin/sodium caseinate had a greater effect on quality control of walnut kernel and its oil than the essential oil encapsulated with β-cyclodextrin. Also, the quality characteristics of walnut kernels and walnut kernel oil packed in vacuum conditions were better than walnut kernels and walnut kernel oil packed in non-vacuum conditions during storage.